Synergistic activity of filtrates of Lactobacillus rhamnosus and Saccharomyces boulardii and antibacterial preparations against Corynebacterium spp. - Isayenko , O. Y. (Regulatory Mechanisms in Biosystems, 2019)
We present the results of the first study of the combined influence of the biologically active substances Lactobacillus rhamnosus GG ATCC 53103 and Saccharomyces boulardii, obtained by the author’s method, and antibacterial agents on Corynebacterium spp. The first area of research was the study of increasing the sensitivity of toxigenic microorganisms to antimicrobial drugs due to the consecutive effects of the structural components and metabolites of L. rhamnosus GG and S. boulardii and antibacterial drugs on Corynebacterium spp. tox+. The greatest increase in the sensitivity of test-cultures of corynebacteria to penicillin (by 19.4 mm), imipenem (by 15.0 mm), vancomycin (by 12.0 mm), gentamicin (by 11.0 mm), ciprofloxacin (by 9.8 mm), erythromycin (by 9.6 mm), cefotaxime (by 9.5 mm) occurred due to the products of lactobacteria and a combination of metabolites of lactobacteria and saccharomycetes. The second area of research was the study of the synergic activity of substances L. rhamnosus GG and S. boulardii and traditional antibacterial drugs manifested by their simultaneous effect on Corynebacterium spp. Maximum potentiation of azithromycin (by 4.6 mm), erythromycin (by 4.5 mm), cefotaxime (by 2.2 mm), ceftriaxone (by 1.6 mm) and ampicillin (by 1.0 mm) relative to corynebacteria was also observed under the influence of lactobacteria metabolites and a combination of lactobacteria and saccharomycetes metabolites. Different degrees of manifestation of the combined action of biologically active substances L. rhamnosus GG and S. boulardii with antibiotics were determined, which depended on the selected combinations, the method of influence on the microorganism, the individual sensitivity of the test-cultures, the activity of the test filtrates and the initial concentration of the producers used to obtain the products of vital activity of lactobacteria and saccharomyces. The presented complexes of structural components and metabolites of L. rhamnosus GG and S. boulardii, obtained without the use of traditional nutrient media, by increasing the bioavailability of pathogenic pathogens can reduce the required concentration of the antibiotic, continuing their use, and suspend the likelihood of pathogens developing resistance to microorganisms. This makes them promising candidates both for the development of "accompaniment-preparations" for antibiotics for the additional therapy of infectious diseases of different etiology, and for the creation of a new direction of antimicrobial agents with multifunctional capabilities. Synergistic activity of filtrates L. rhamnosus GG and S. boulardii and antibacterial preparations against Corynebacterium spp.